Análisis de la cultura organizacional y su incidencia en el desempeño laboral de los servidores públicos del GAD del cantón Chone - Taffur Lucas, Miguel Ángel (2022)
The present research was developed in the Autonomous Decentralized Government in canton Chone and the main objective was to analyze the organizational culture and its impact on the work performance of public servants, for its fulfillment we proceeded to use the inductive, deductive, analytical and synthetic method, also the application of research techniques such as interview and survey that helped to collect information directly from those involved in the research, in order to collect more relevant and reliable information. So that, we proceeded in the correct achievement of each of the objectives of the research and its activities, observing certain shortcomings that would be affecting the proper functioning of the institution, such as the little importance to the comments and suggestions of the staff, they are not given the relevant and adequate information for the performance of their daily activities, the essential tools provided to efficiently perform their work are scarce, in addition to the fact that the staff is not continuously undergoing training to improve their skills and abilities as they should, generating that the members of the institution are unmotivated, with an unsuitable environment to perform their various functions at all levels of the institution. In conclusion, it is essential to implement appropriate actions, so that a continuous improvement plan is proposed, directed to the competent authorities of the GAD in Chone canton with strategies for strengthening the organizational culture and its impact on the work performance of public servants of the same.